2017
DOI: 10.1007/s12192-016-0740-2
|View full text |Cite
|
Sign up to set email alerts
|

Moderate endoplasmic reticulum stress activates a PERK and p38-dependent apoptosis

Abstract: The endoplasmic reticulum (ER) has the ability to signal organelle dysfunction via a complex signaling network known as the unfolded protein response (UPR). In this work, hamster fibroblast cells exhibiting moderate levels of ER stress were compared to those exhibiting severe ER stress. Inhibition of N-linked glycosylation was accomplished via a temperature-sensitive mutation in the Dad1 subunit of the oligosaccharyltransferase (OST) complex or by direct inhibition with tunicamycin (Tm). Temperature shift (TS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…Inhibition of P38 activation was sufficient to reduce hamster fibroblast cells death and apoptosis induced by moderate tunicamycin. 31 In our study, C3G reduced the high levels of p-P38 induced by UVA.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Inhibition of P38 activation was sufficient to reduce hamster fibroblast cells death and apoptosis induced by moderate tunicamycin. 31 In our study, C3G reduced the high levels of p-P38 induced by UVA.…”
Section: Discussionsupporting
confidence: 58%
“…Huang et al and Hsu et al found that p‐P38 was significantly increased in HDFs after UVA irradiation, consistent with the findings of this study. Inhibition of P38 activation was sufficient to reduce hamster fibroblast cells death and apoptosis induced by moderate tunicamycin . In our study, C3G reduced the high levels of p‐P38 induced by UVA.…”
Section: Discussionsupporting
confidence: 56%
“…S5 ). The lack of expression was accompanied by a massive phosphorylation of p38, suggesting cellular endosomal stress activation, possibly due to a trafficking impairment that can lead to downstream stress signaling 37 . Two sequence polymorphisms in the ectodomain of the cloned full-length chicken TLR5 and the ch/h chimera were identified by Sanger sequencing in comparison to the reference sequence in the NCBI database (NP_001019757.1) (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…UPR is situated to mediate both adaptive and maladaptive mechanisms that account for the diverse phenotype observed during gentamicin-induced proximal tubule cell death. UPR normally limits cell stress by increasing protein refolding and mitigating CHOP activation, a major contributor to cell death 69,70 . However, if cell stress is prolonged or irreversible, the balance between misfolded proteins and available chaperones is perturbed.…”
Section: Discussionmentioning
confidence: 99%